Methodical Approach to the Evaluation of Innovative Potential of Light Industry of Ukraine - Goncharenko, O.G.; Anishchenko, V.O.; Sirenko, K.Yu. (Science and Innovation, 2024)
Introduction. In the market conditions, under aggravating competition in the industrial market, a comprehensive assessment of the innovation potential of light industry is a relevant and practically significant problem. So far, no general approach has been developed to assess the innovative potential of industrial entrepreneurship, and the level of theoretical, methodological and practical solution to this aspect has a little effect on the business activities. Problem Statement. Innovative development of corporations is an unexplored trend. This fact hinders increasing the competitiveness of industrial corporations and strengthening their competitive market position. In view of this, the problem of complex evaluation of the innovation potential of light industry is very relevant, since its solution can ensure the objectivity of economic results and allow corporations to effectively organize innovation activities. Рurpose. To develop a methodological approach to the evaluation of the innovation potential of light industry, which allows corporations to comprehensively summarize their economic results and to make optimal management decisions. Materials and Methods. A methodological approach to measuring the innovation potential of light industry using the taxonomic method has been used. Results. The components of innovation potential have been identified and groups of indicators have been formed and calculated according to the characteristic criteria. In order to evaluate this indicator, the principles for the formation of a system of indicators in each area have been proposed. The main stages of calculating the innovation potential of light industry have been highlighted. Conclusions. Based on the calculations, various approaches to defining the concept of innovation as a fundamental factor in the progressive socio-economic development of the country have been generalized. The system of indicators has been formed and the developed integral indicators of innovation potential of light industry have been simulated.